Effect of drying process on marupá wood color - Gonçalez, Joaquim Carlos; Bezerra Marques, Márcia Helena; Sousa Karas, Maria Cristina; Janin, Gerard; Gomes Ribeiro, Patricia (Maderas. Ciencia y Tecnología, 2025)
This research was developed after consultations with tropical timber exporters, who were facing problems with the colors of the species under study. This work aimed at characterizing Simarouba amara tropical wood color and verifying possible differences between the colorimetric parameters determined for the tangential and the radial directions of the wood, kiln-dried and air-dried. S. amara wood presents a grayish-white color. This color is mainly characterized by the b* coordinate (yellow pigment). Depending on the drying method used, the wood may present different colors for both tangential and radial directions. In both drying methods conducted, the wood presented lighter color in the tangential direction. Kiln-drying appeared to reduce S. amara wood lightness.